AUTOMATED AND COMMERCIALIZED REALITY CONSTRUCTIONS: GOVERNANCE BY ALGORITHMS ON THE INTERNET - Latzer, Michael; Just, Natascha (AoIR Selected Papers of Internet Research, 2015)
This paper focuses on the governing effects of Internet algorithms in information societies. It analyzes the often-neglected significance, role and challenges of (software) technology in the co-evolutionary institutionalization of governance. According to the IR16 conference theme Digital Imaginaries, this paper scrutinizes the topic: relationship between technology and the imaginary. More precisely, it explores the reality construction by algorithmic selection on the Internet that includes and at the same time goes far beyond the formation of collective imaginaries of networked technologies. The paper highlights the interplay with and the differences to reality constructions by traditional mass media, and investigates the societal and democratic consequences of this growing Internet phenomenon.